Validity of teaching materials of sub-concepts of structure and function plants tissue in high school based on android applications - Noorhidayati Noorhidayati; Riya Irianti; Siti Norridzati (Master Program of Biology Education, Universitas Lambung Mangkurat, Banjarmasin, Indonesia, 2023)
The validation process is crucial in developing teaching materials to see the suitability of teaching materials with the expected learning outcomes. Teaching materials that have been declared valid can be used in the learning process. Technology-based teaching materials such as android application-based ones are one of the alternative teaching materials suitable for use in the learning process in the era of society 5.0 education. This study aimed to analyse the validity of teaching materials for the sub-concept of the structure and function of tissues in plants in high schools based on android applications. A quantitative descriptive research method was employed to find information on the validity of the teaching materials compiled. The study used a 4D development model. The subjects of the validity data were three validators (expert judgment), namely two lecturers and one partner teacher. The results showed that the teaching materials compiled obtained a suitability score of 4.45 and the results of the feasibility test of 4.35. Hence, the average validity score was 4.4, with a very valid category. The valid android application-based teaching material is feasible in the learning process with more flexibility.Abstrak Proses validasi pada pengembangan bahan ajar diperlukan untuk melihat kesesuaian bahan ajar dengan capaian pembelajaran yang diharapkan. Bahan ajar yang telah divalidasi dan dinyatakan valid dapat digunakan dalam proses pembelajaran. Bahan ajar berbasis teknologi seperti berbasis aplikasi android merupakan salah satu alternatif bahan ajar yang sesuai untuk digunakan pada proses pembelajaran di era pendidikan society 5.0. Tujuan penelitian ini adalah menganalisis validitas bahan ajar sub konsep struktur dan fungsi jaringan pada tumbuhan d SMA berbasis aplikasi android. Metode penelitian deskriptif kuantitatif, untuk menemukan informasi validitas bahan ajar yang disusun. Penelitian menggunakan model pengembangan 4D. Subyek data validitas yaitu tiga orang validator (expert judgement) yaitu dua orang dosen dan dan orang guru mitra. Hasil penelitian menunjukan bahwa bahan ajar yang disusun memperoleh skor kesesuaian sebesar 4.45 dan asil uji kelayakan sebesar 4.35. Maka, rerata skor validitas 4.4 dengan kategori sangat valid. Materi pelajaran berbasis aplikasi android layak digunakan dalam proses pembelajaran dengan lebih fleksibel.